Hybrid Yarns: Highly Conductive Carbon Nanotube‐Graphene Hybrid Yarn (Adv. Funct. Mater. 37/2014). (October 2014) - Foroughi, Javad; Spinks, Geoffrey M.; Antiohos, Dennis; Mirabedini, Azadehsadat; Gambhir, Sanjeev; Wallace, Gordon G.; Ghorbani, Shaban R.; Peleckis, Germanas; Kozlov, Mikhail E.; Lima, Marcio D.; Baughman, Ray H.
<x xml:space="preserve">Abstract</x> A new process to manufacture highly conductive textile yarn for use in wearable electronics by providing flexible fiber electrodes for energy storage, low‐loss interconnects, sensors, and artificial muscles is described by J. Foroughi and team on page 5859. Graphene dispersions are electrospun onto the continuously drawn multi‐walled carbon nanotube sheets and transformed into yarn filaments by twist insertion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>